Multiscale Impacts of Anthropogenic and Climate Changes on Tropical and Mediterranean Hydrology - Descroix, Luc; Mahé, Gil; Laraque, Alain; Ribolzi, Olivier; Lacombe, Guillaume (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The atmospheric part of the water cycle is accelerating, affecting hydrological dynamics, especially in tropical and Mediterranean areas, where landscapes, soils and territories are particularly vulnerable to global warming and land use changes. Across four continents and a dozen of different regions or basins, this SI strives to highlight the environmental and societal vulnerabilities and their links with the water cycle. The basins of three of the greatest basins in the world in terms of streamflows-the Amazon River, the Orinoco River and the Congo River-show their unexpected behaviors. This book aims to present past and present status to improve future land and water management.